Collective Memory, Ritual and Symbols as Cultural Defense of Traditional Muslim Society in Semarang, Central Java - Tedi Kholiludin (Jurnal Sosiologi Agama, 2025)
This paper explores how a community maintains its identity when it has to deal with changes. By using traditional Muslims in the city of Semarang as the group studied, this study examines how this group builds cultural defenses. The data in this sociological research were obtained through literature study, observation and interviews. Once collected, the data were analyzed descriptively. By using a cultural defense framework, traditional Muslim groups in Semarang build defense with three aspects; collective memory, rituals and symbols. All three are presented as an attempt to deal with modernity.